Pengembangan Media Evaluasi Interaktif Berbasis Blooket pada Materi Sistem Pencernaan Kelas XI - Rivatul Mauluddia; Nurmala Hindun (Universitas Tribhuwana Tunggadewi, 2026)
Digital transformation in education calls for updates to assessment tools, particularly in Biology, which covers abstract topics such as the human digestive system. The conventional approaches used to date tend to reduce student engagement and hinder deep conceptual understanding. This study aims to develop and test the feasibility of an interactive assessment tool based on the Blooket platform for 11th-grade high school students. Using the Research and Development (RD) method with the 4D development framework (Define, Design, Develop, Disseminate), this study involved a Biology teacher and 26 students at SMAS Islam NU Pujon. Data were collected through expert validation instruments and user response questionnaires The research findings confirmed that the developed media is of high quality, with a feasibility rating of 94% from media experts and 90% from subject matter experts. The educator provided very positive feedback with a score of 96%. Meanwhile, student responses yielded an average score of 4.40 on a 5-point scale. In detail, the visual aesthetics and readability aspects achieved the highest score (4.65), while the clarity of usage instructions received the lowest score (4.19), though it remained in the “very good” category. Based on this data, it can be concluded that the use of Blooket as an assessment tool is highly appropriate and effective for reinforcing conceptual understanding of the material and creating a more dynamic and participatory biology learning environment.